Performance of glass-ACP façade system in a full-scale real fire test in a G+2 structure. (2017) - Gandhi, Pravin; Jagdish, V; Karthikeyan, G; Chakravarthy, Aravind; Nakrani, Dharmit; Ghoroi, Chinmay; Srivastava, Gaurav
Abstract: Glass façade are used very commonly in modern construction due to their role in energy conservation in addition to improving the aesthetics. However, they can easily become vehicles for movement of fire along the building, as has been observed in several past fire accidents. Thus, assessment of façade systems in real fire scenarios is important. Keeping this in mind, a full scale G+2 storey steel frame building has been constructed within the campus of IIT Gandhinagar located in Gujarat, India, where different façade systems can be tested under real fire scenarios. The building has three fire compartments in each storey of plan dimensions 10'×20' with a storey height of 10'. Fire scenarios are developed using real office furniture (sofa sets, reception desks, curtains, carpets, etc.) in accordance with the National Building Code of India. The building has been instrumented with K-type thermocouples, video and thermal imaging cameras. This study presents observations and inferences related to the performance of a façade system of toughened glass and aluminium composite panels (ACP). The fire was initiated inside the compartment and was allowed to grow naturally, break the façade of ground floor, and propagate to the higher floors through the so-called leap-frog effect. It was observed that the glass panels did not break due to fire but fell to ground in intact form due to expansion of the cladding aluminium frame. ACP boards allowed the inner insulation polymer to be exposed to fire and subsequently initiated a small secondary fire at the ground level outside the building. Severe deformation and melting of the cladding aluminium frame was observed as the temperatures went well beyond the melting point of aluminium. It is expected that the observations presented in this study will enable improvements in the fire safety requirements of façade systems.